Increasing the Economic Sustainability of the Territory on the Basis of Development of Cotton-Textile Clusters - Jalilova, Oysudabonu (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the development of cotton and textile activities in the regions of the country and the effective organization of cluster activities. Suggestions for the development of cotton-textile clusters are made.